Quasi-Coherent Noise Jamming to LFM Radar Based on Pseudo-random Sequence Phase-modulation - Tai, Ning; Pan, Yujian; Yuan, Naichang (Společnost pro radioelektronické inženýrství, 2015)
A novel quasi-coherent noise jamming method is proposed against linear frequency modulation (LFM) signal and pulse compression radar. Based on the structure of digital radio frequency memory (DRFM), the jamming signal is acquired by the pseudo-random sequence phase-modulation of sampled radar signal. The characteristic of jamming signal in time domain and frequency domain is analyzed in detail. Results of ambiguity function indicate that the blanket jamming effect along the range direction will be formed when jamming signal passes through the matched filter. By flexible controlling the parameters of interrupted-sampling pulse and pseudo-random sequence, different covering distances and jamming effects will be achieved. When the jamming power is equivalent, this jamming obtains higher process gain compared with non-coherent jamming. The jamming signal enhances the detection threshold and the real target avoids being detected. Simulation results and circuit engineering implementation validate that the jamming signal covers real target effectively.
Keywords: LFM; electronic countermeasure; DRFM; pseudo-random sequence; interrupted-sampling